The Personality of Children's Dramaturgy by Galimjan Gyilmanov - Nureeva, Gulshat Ilshatovna; Mingazova, Liailia Ihsanovna; Khabutdinova, Milyausha Mukhametsyanovna; Sayfulina, Flera Sagitovna (International Journal of Criminology and Sociology, 2022)
the main aim of the study is to systematize materials on the creative work of Galimyan Gilmanov, the Tatar writer of the second half of the twentieth century. Until now, the attention of literary scholars has been riveted to the "adult" prose of the writer (such novels as "Evil Spirits," "Flying People"). G. Gilmanov managed to declare himself as a children's poet, prose writer, and a playwright. The novelty of the work is to study the contribution of the writer to the development of modern children's drama. The work proved that G. Gilmanov works in traditional technology. In his plays, a linear plot is used. Moral issues dominate the content. The central conflict in his plays is the struggle between good and evil, the clash of individualism and collectivism. The character system is dominated by the contrast between positive and negative characters. A favorite technique for organizing text is the antithesis. The playwright actively uses the "speaking name" technique to characterize the characters.